Bestari Partners - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.- Papers must be a real work of the author.- Papers has never been published in other media.- Papers must contain discussion about Infrastructure & Facility Asset Management.- Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.- The paper have to take reference from Journal minimum 3 papers.- Paper lengths are limited in 8-16 pages.- Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of the following.- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Policy- I & F Planning- I & F Administration Aspects- I & F Operation System- I & F Maintenance System- I & F Evaluation Technique- I & F Disposal- I & F Economical Aspect- I & F Financial Aspect- I & F Management Organization- I & F Spatial Aspects and Environmental AspectsReviewerHitapriya Suprayitno, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaRia Asih Aryani Soemitro, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaData Iranata, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaAchmad Wicaksono, University of Brawijaya (UM), Malang, IndonesiaVita Ratnasari, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaEko Budi Santoso, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaI Putu Artama Wiguna, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia